Climate Variability in West Africa : Official Development Assistance Impact on Food Security - Ndonougbo, Yevess Da; Agbodji, Ega Akoété A (DEMO, 2020)
The objective of this paper is to assess the effect of official development assistance in the mitigation of climate variability on food security in West African. Using panel data from 14 countries over the period 1990 to 2016, the results of econometric estimates show that the negative effect of rainfall variability on food supply in the countries of the region is indirectly reduced with official development assistance. Moreover, official development assistance alone does not seem to have a significant effect on the food supply of countries in this region. Thus, official development assistance is a factor that helps to mitigate the effects of climate change and should be given greater consideration in climate change adaptation policies in order to reduce the effects of climate change on food security in the countries of the region.(original abstract)